2007
DOI: 10.1152/ajpregu.00784.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased duration of simulated childbirth injuries results in increased time to recovery

Abstract: Stress urinary incontinence (SUI) development is strongly correlated with vaginal childbirth, particularly increased duration of the second stage of labor. However, the mechanisms of pelvic floor injury leading to SUI are largely unknown. The aim of this study was to determine the effects of increased duration of vaginal distension (VD) on voiding cystometry, leak point pressure testing, and histology. Sixty-nine virgin female rats underwent VD with an inflated balloon for either 1 or 4 h, while 33 age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 46 publications
7
90
1
Order By: Relevance
“…The balloon then was slowly inflated with 3ml sterile water and a single stitch (3-0 silk) was placed in the skin near the vagina to secure the catheter in place, as we have done previously. 3,5 After the chosen duration, the stitch was removed, the balloon deflated, and the catheter removed.…”
Section: Vaginal Distension (Vd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The balloon then was slowly inflated with 3ml sterile water and a single stitch (3-0 silk) was placed in the skin near the vagina to secure the catheter in place, as we have done previously. 3,5 After the chosen duration, the stitch was removed, the balloon deflated, and the catheter removed.…”
Section: Vaginal Distension (Vd)mentioning
confidence: 99%
“…[2][3][4] Previous studies have demonstrated increased tissue damage with increasing duration of VD. 3,5 We have previously demonstrated that one stem cell homing factor, monocyte chemotactic protein-3 (MCP3), is upregulated in vaginal and urethral tissues immediately after VD in virgin rats. 4 However, studies comparing molecular markers of tissue repair after VD of differing durations are lacking.…”
Section: Introductionmentioning
confidence: 98%
“…More importantly, in labor simulation computer and animal models, the fetal head and biomechanical labor forces cause direct stretch and compression injuries to the pelvic floor muscles during delivery that contributes to progressive deterioration in muscle function. Both muscle injuries were found to develop at a lower tissue elasticity threshold than that observed in normal parturition [5,6]. The likelihood of indirect neural and muscular injuries is obviously increased when labor dystocia is not detected and treated promptly, or when aggressive maneuvers are used to expedite delivery, such as forcible manual compression of the uterus or dilatation of the vagina and excessive traction by the obstetric forceps or ventouse.…”
mentioning
confidence: 97%
“…Moreover, the optimum ratio between the length of episiotomy and the length of perineum that can reliably predict minimal perineal damage is not known [1]. Despite the availability of this information, episiotomy, particularly the routine procedure, is performed more frequently in developing countries than in the West [3].Over the past two decades, neurophysiological and experimental research has revealed that vaginal delivery damages the pelvic floor muscles through mechanisms unrelated to traumatic disruption [4][5][6]. During the second stage of labor, the pudendal nerve is compressed by the fetal head against the ischial spines, causing entrapment neuropathy and partial denervation of the striated pelvic floor muscles [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation